Influence of sowing dates and nutrient management on growth and yield of spring green gram (Vigna radiata L.) under heat and moisture stress conditions in Punjab - Soumalya, Mallick; Anita, Jaswal; Sarang, S Hari (Plant Science Today, 2026)
This study was carried out in the spring of 2025 at the agricultural farms of Lovely Professional University, Phagwara, Punjab, to assess the impact of sowing dates and nutrient management on the growth and yield of spring green gram (Vigna radiata L.) under conditions of heat and moisture stress. The experiment utilized a factorial randomized block design including two sowing dates (24 March and 08 April 2025) and nine nutrient management treatments, each replicated three times. The results indicated that growth characteristics, including plant height, leaf number, leaf area, fresh weight, dry weight, branch number plant-1 and chlorophyll content, were strongly affected by nutrient management, whereas sowing dates had comparatively slight but significant effects. The combination of sugarcane bagasse biochar at 5 t ha-1 with soil applications of cobalt (1 kg ha-1) and molybdenum (1.5 kg ha-1), combined with 100 % RDF (N7), yielded the highest growth parameters, yield attributes and seed yield (1450.65 kg ha-1). Early sowing (24 March) resulted in a comparatively higher seed yield (1313.38 kg ha-1) than late sowing (1278.50 kg ha-1), demonstrating the benefit of mitigating late-season temperature stress. Correlation studies revealed strong positive relationships among temperature, soil moisture and crop growth traits; however excessive humidity and wind speed negatively influenced yield. The results highlight that the combination of biochar with micronutrient application and timely sowing can significantly reduce heat and moisture stress, thereby improving the production of spring green gram in subtropical environments.